2020
DOI: 10.1038/s41467-020-18935-2
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D deficiency in mammary epithelium transiently stalls breast cancer by interference with mTORC1 signaling

Abstract: Cathepsin D (CTSD) is a lysosomal protease and a marker of poor prognosis in breast cancer. However, the cells responsible for this association and the function of CTSD in cancer are still incompletely understood. By using a conditional CTSD knockout mouse crossed to the transgenic MMTV-PyMT breast cancer model we demonstrate that CTSD deficiency in the mammary epithelium, but not in myeloid cells, blocked tumor development in a cell-autonomous manner. We show that lack of CTSD impaired mechanistic Target of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 63 publications
1
47
0
1
Order By: Relevance
“…Previous studies have found that the overexpression of cathepsin B leads to the invasiveness and metastasis of breast cancer, pancreatic cancer, HCC, and colorectal cancer, by activating the ErbB oncogenic signaling pathway 11 – 14 . The cytosol concentration of cathepsin D was found to have a strong influence on metastasis in breast cancer 15 , 16 . In addition, cathepsin K was found to have a high correlation with the progression of prostate cancer and breast cancer 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the overexpression of cathepsin B leads to the invasiveness and metastasis of breast cancer, pancreatic cancer, HCC, and colorectal cancer, by activating the ErbB oncogenic signaling pathway 11 – 14 . The cytosol concentration of cathepsin D was found to have a strong influence on metastasis in breast cancer 15 , 16 . In addition, cathepsin K was found to have a high correlation with the progression of prostate cancer and breast cancer 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Cells were stained with 0.1% crystal violet, and absorbance was measured at 570 nm. APQQEALPDE [18][19][20][21][22][23][24][25][26][27] Glu-C 0.98 (2) APQQEALPDETE [18][19][20][21][22][23][24][25][26][27][28][29] Glu-C 0.88 (13) APQQEALPDETEVVE [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Glu-C 1.12 (6) APQQEALPDETEVVEE [18][19][20][21][22][23][24][25][26][27][28][29][30]…”
Section: Cell Adhesion Migration Endothelial Transmigration and Invmentioning
confidence: 99%
“…Purified 52-kDa cath-D auto-activates in acidic conditions, giving rise to a catalytically active 51-kDa pseudocath-D form that retains the 18 residues (27-44) of the pro-segment [14]. Cath-D affects the tumor and its microenvironment by increasing BC cell proliferation [13,[15][16][17][18], and by stimulating mammary fibroblast outgrowth [19,20], angiogenesis [15,21], and metastasis formation [17]. However, little is known about the molecular mechanisms and the substrates involved in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsin D dianggap sebagai penanda prognosis independen pada jenis kanker dan peningkatan Cathepsin D berhubungan dengan meningkatnya keganasan dari kanker termasuk kanker payudara, kanker ovarium, kanker lambung dan kanker prostat. Hal ini tentu saja mendasari bahwa Cathepsin D merupakan target potensial untuk mengobati kanker (Ketterer et al, 2020;Xu et al, 2017).…”
unclassified